2006
DOI: 10.1159/000089211
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of SARS Coronavirus by Means of Povidone-Iodine, Physical Conditions and Chemical Reagents

Abstract: The efficacy of several povidone-iodine (PVP-I) products, a number of other chemical agents and various physical conditions were evaluated for their ability to inactivate the severe acute respiratory syndrome coronavirus (SARS-CoV). Treatment of SARS-CoV with PVP-I products for 2 min reduced the virus infectivity from 1.17 × 106 TCID50/ml to below the detectable level. The efficacy of 70% ethanol was equivalent to that of PVP-I products. Fixation of SARS-CoV-infected Vero E6 cells with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
456
1
19

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 412 publications
(495 citation statements)
references
References 17 publications
10
456
1
19
Order By: Relevance
“…All formulations reduced the viral infectivity under the detectable level after 2 min of contact-time. The same result was obtained with 70% ethanol in 1 min [129]. …”
Section: Antisepsis-disinfection: An Efficient Weapon With Room Fsupporting
confidence: 79%
“…All formulations reduced the viral infectivity under the detectable level after 2 min of contact-time. The same result was obtained with 70% ethanol in 1 min [129]. …”
Section: Antisepsis-disinfection: An Efficient Weapon With Room Fsupporting
confidence: 79%
“…Seventy percent ethanol was found in 1 study to inactivate SARS by .3 log 10 . 27 Rabenau et al 9 reported a log 10 reduction factor of .5 after 30-second contact time using 78% ethanol and 70% propoanol, a reduction that was actually greater than what they observed with other germicides classified as chemical steriliants. These results support the findings of this study that ethanol-based disinfectants are efficacious against coronaviruses.…”
Section: Discussionmentioning
confidence: 85%
“…It also increases the available data both for disinfectants that have previously been studied with SARS Co-V and disinfectants that have not. Previous studies using SARS have evaluated benzalkonium chloride and magnesium monoperphthalate-based products, 16 povidone iodine, 27 formalin, and glutaraldehyde. 31 This current study included sodium hypochlorite and a phenolic, which have not been evaluated in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…The incubation times did not appear to correlate with the virus titre. Studies on severe acute respiratory syndrome coronavirus (SARS-CoV) showed that incubating the virus at 568C for 60 min or longer reduced the titre to undetectable levels (Kariwa et al, 2006). However, coronavirus inactivation is apparently dependent on the amount of protein in the sample.…”
Section: Discussionmentioning
confidence: 99%